Use of Teriparatide Prior to Lumbar Fusion Surgery Lowers Two-year Complications for Patients With Poor Bone Health. (16th November 2020) - Yolcu, Yagiz U; Zreik, Jad; Alvi, Mohammed A; Wanderman, Nathan; Carlson, Bayard; Nassr, Ahmad; Fogelson, Jeremy L; Elder, Benjamin D; Freedman, Brett A; Bydon, Mohamad
Abstract: INTRODUCTION: Poor bone health can create challenges in management which are amplified for patients undergoing spinal fusion due to potential risks of delayed healing and increased complications. Although previously shown to improve outcomes postoperatively, the impact of preoperative teriparatide use on long-term complications remains unclear. METHODS: Patients undergoing any lumbar fusion surgery at a single institution between 2008 and 2018 were identified, followed by screening for a diagnosis of osteoporosis or osteopenia prior to lumbar fusion. The patient cohort was subsequently divided into two groups as teriparatide and non-teriparatide group. Baseline demographics, patient and surgery related factors, and two-year complications were collected through a retrospective chart review. Multivariable logistic regression was performed to evaluate the association between teriparatide usage and development of any related postoperative complication. RESULTS: A total of 42 and 114 patients were identified for the teriparatide and nonteriparatide groups, respectively. The median age (IQR) for the teriparatide group was 62 years (55.8-68.8), while the non-teriparatide group had a median (IQR) age of 70 years (64- 75.8). Overall, there were no statistically significant differences in terms of individual complications between the groups. However, the rate of encountering any complication at two-year follow-up was significantly lower for patients on teriparatide ( P  = .049). CONCLUSION: Teriparatide use prior to lumbar fusion procedures resulted in a reduced rate of individual complications as well as an association with decreased related 2-year complications. While these results suggest improved outcomes in patients with osteopenia and osteoporosis when pre-treating with teriparatide, there may be a treatment bias due to the retrospective nature of the study. Future prospective studies are needed to determine optimal utilization and timing of the pretreatment.